Buddhism and Islam : Mutual Engagements in Southeast Asia and Japan - Obuse, Kieko, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2024)
Buddhist-Muslim relations are usually seen as inherently confrontational. This book challenges the view of Buddhism and Islam as fundamentally irreconcilable by exploring the diverse ways representatives of the two traditions have engaged each o